2018
DOI: 10.1177/1403494818801507
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial job demand and control: multi-site musculoskeletal pain in Swedish police

Abstract: Aims: Police have a high prevalence of musculoskeletal disorders. While physical factors contributing to this have been explored, little is known regarding the contribution of the psychosocial work environment. This study explores the association between elements of the JDC model, social support and multi-site musculoskeletal pain among Swedish police. Methods: In this cross-sectional study, responses from 4185 police were collected using a self-administered online survey. The survey included questions on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 32 publications
3
24
0
2
Order By: Relevance
“…For example, in a longitudinal study of 5136 employees from the Netherlands, Oakman et al [19] found that high job demands increased the risk of musculoskeletal pain by almost 60% during a four-year measurement period. Our findings are also consistent with several cross-sectional studies related to this field [7,12,15,16,17,21,23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, in a longitudinal study of 5136 employees from the Netherlands, Oakman et al [19] found that high job demands increased the risk of musculoskeletal pain by almost 60% during a four-year measurement period. Our findings are also consistent with several cross-sectional studies related to this field [7,12,15,16,17,21,23].…”
Section: Discussionsupporting
confidence: 93%
“…Emerging evidence suggests that work conditions such as workload (mechanical and physical) and psychosocial work stressors (e.g., high job demands and low support) are strongly linked with musculoskeletal pain [7,14,15,16,17,18,19,20,21,22,23]. The number of ARP has been related to physical workload [21], exposure to manual material handling, and awkward work postures [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later social support was added to the model as a third dimension, postulating that high social support could buffer high strain work situations (Karasek & Theorell, 1990). The JDC model is supported by several studies investigating MSP in wage-earners in general (Larsen et al, 2019;Vanroelen et al, 2009), as well as in cabin crew (Lee et al, 2008;Wahlstedt et al, 2010).…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have documented PSYJS to be associated with MSP (Lang et al, 2012;Larsen et al, 2019). A commonly used model to explain how psychosocial factors affect MSP is the Job Demand Control Model (Karasek & Theorell, 1990;Larsen et al, 2019). The JDC model hypothesize that a high strain job, e.g., high psychological demands and low control, could lead to MSP.…”
Section: Introductionmentioning
confidence: 99%